A comparison of pure tone thresholds and distortion product otoacoustic emission measures in patients with Tuberculosis receiving aminoglycosides - Petersen, Lucretia (Division of Communication Sciences and Disorders, 2014)
Includes bibliographical references (leaves 116-131).